Artefak budaya narasi lisan dan visual Indonesia menuju komik dan animasi global - Rohman, Moch. Abdul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
Oral and visual narratives in local culture contain profound meanings and philosophical values that require deeper analysis. Influences from other countries’ cultures are evident in many literary and creative works, such as novels, comics, children’s stories, as well as multimedia productions including films and game software. Through the use of oral narrative cultural artifacts and visual cultural artifacts, both forms are expected to inspire the creation of scripts or stories and visual designs in comics and animated films that promote Indonesian local wisdom.